Carbon-coated, hierarchically mesoporous TiO2 microparticles as an anode material for lithium and sodium ion batteries - Devina, Winda; Nam, Dongho; Hwang, Jieun; Chandra, Christian; Chang, Wonyoung; Kim, Jaehoon (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Hierarchically porous anatase TiO2 microparticles are synthesized in supercritical methanol (scMeOH) in the presence of organic surface modifiers such as oleylamine, oleic acid, and poly(ethylene glycol)methyl ether/citric acid (PEGME/CA) mixture. Primary TiO2 nanoparticles (5-9 nm) that loosely aggregate to form secondary micron-sized particles (0.2-1.5 mu m) are obtained in the presence of PEGME/CA. The surface modifier aids the effective suppression of undesirable crystal growth because their molecules cap the surfaces of growing particles in scMeOH. An ultrathin, conformal and uniform carbon layer with 1-2 nm thickness is then formed on the surface of the TiO2 particles by heat treatment. The carbon-coated TiO2 particles delivers 231 mAh g(-1) at 0.1 C after 50 cycles and 85 mAh g(-1) at 10 C in a lithium-ion battery cell, 275 mAh g(-1) at 0.1 C after 50 cycles, 40 mAh g(-1) at 10 C, and high capacity retention of 94% after 450 cycles in a sodium-ion battery cell. The excellent electrochemical performance of the TiO2 particles is attributed to the small crystallite size, continuous electronic network formed by the close contact of individual carbon-coated primary TiO2 particles, and the effective penetration of the mesopores by the electrolytes. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: SOLID-ELECTROLYTE INTERPHASE; HIGH-RATE PERFORMANCE; EXPOSED 001 FACETS; ANATASE TIO2; SUPERCRITICAL METHANOL; OXIDE NANOPARTICLES; HIGH-CAPACITY; METHYL ESTERIFICATION; CEO2 NANOCRYSTALS; FACILE SYNTHESIS